Different Levels in Orexin Concentrations and Risk Factors Associated with Higher Orexin Levels: Comparison between Detoxified Opiate and Methamphetamine Addicts in 5 Chinese Cities. (12th September 2013) - Zhang, Haoran; Lian, Zhi; Yan, Shiyan; Bao, Yanping; Liu, Zhimin
Abstract : This study sought to explore the degree of orexin levels in Chinese opiate and methamphetamine addicts and the differences between them. The cross-sectional study was conducted among detoxified drug addicts from Mandatory Detoxification Center (MDC) in five Chinese cities. Orexin levels were assayed with radioimmunoassay (RIA). Mann-Whitney U test and Kruskal-Wallis test were used to detect differences across groups, and logistic regression was used to explore the association between orexin levels and characteristics of demographic and drug abuse. Between November 2009 and January 2011, 285 opiates addicts, 112 methamphetamine addicts, and 79 healthy controls were enrolled. At drug withdrawal period, both opiate and methamphetamine addicts had lower median orexin levels than controls, and median orexin levels in opiate addicts were higher than those in methamphetamine addicts (all above P < 0.05 ). Adjusted odds of the above median concentration of orexin were higher for injection than "chasing the dragon" (AOR = 3.1, 95% CI = 1.2–7.9). No significant factors associated with orexin levels of methamphetamine addicts were found. Development of intervention method on orexin system by different administration routes especially for injected opiate addicts at detoxification phase may be significant and was welcome.